Radiometer for measuring gamma-radiation, beta-particles and neutrons based on DRG-05M dosimeter - V. M. Venedyktov; V. М. Shevel; V. А. Libman (Ядерна фізика та енергетика)
As a result of the modernization of the DRG-05M dosimeter, a convenient device was obtained, which allows estimating the level of gamma- and X-ray radiation, beta-particles, and neutrons without changing the detector heads. Two devices were manufactured and a third one was prepared for metrological certification.